Subjective Vitality and its Relationship to the Counseling Creativity of Educational Counselors - Fatimah Adil Dakhil Al-Mhesin ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study aims to investigate the subjective vitality and its relationship to the counseling creativity of educational counselors. In addition, it aims to investigate the individual differences between educational counselors according to the gender variable . The study sample comprises 200 counselors . SubjectiveVitality Scale by Ryan and Frederick (1997) and Counseling Creativity Scale by Al-Walidi and Arnout ( 2017) have been utilized to collect data.DOI /10.54633/2333-021-042-027